The Influence of NPF, ROA, CAR, and BOPO on Financial Distress at Sharia Rural Bank in Indonesia - Aris Athoillah Sholahudin; Barianto Nurasri Sudarmawan (Universitas Islam Negeri Alauddin Makassar, 2024)
This research was motivated by the problem of financial performance at BPRS experiencing a decrease but the number of units experiencing an increase. The purpose of this study is to analyze the effect of NPF, ROA, CAR, and BOPO on financial distress at Sharia Rural Banks (BPRS) in Indonesia. BPRS is an important financial institution that supports Micro, Small and Medium Enterprises (MSMEs) in Indonesia. However, in recent years, the financial performance of BPRS has shown a worrying trend, such as increasing NPF and BOPO ratios and decreasing ROA. This study uses data from the financial statements of BPRS registered with the Financial Services Authority (OJK) for 2019 to 2023. The analysis method uses panel data regression with EViews. This study obtained the results that NPF and BOPO have a significant positive effect on financial distress, ROA shows a significant negative effect, and CAR doesn’t have a significant effect in this study. It’s hoped that this study can provide recommendations to BPRS to improve operational efficiency and manage good financial risks in order to avoid bankruptcy and can continue to contribute to the development of the community's economy.